A educação do campo como projeto político e prática social : o caso do Colégio Estadual do Campo Izaias Rafael da Silva - Bolonhezi, Camilla Samira de Simoni (2017)
This study aims to analyze the process of construction, conquest and development of rural education as a public educational policy, as well as to understand the historical process in which the struggle for the right and access to education in and to the countryside took place specifically in the State of Paraná, between the beginning of the 1980?s until nowadays. The research theme was evidenced in the search for an understanding of the dynamics that public policy, social and focused policies in Brazil, as well as to relate them to the administration and action of the organized social movements. Focusing on understanding the influence and action of the social movements in the construction and maintenance of such policies, it was necessary to consider the fact that the object of study is in motion (in this case the Country Education). This object is surrouded by active and politically experienced subjects, imbibed by the mysticism of the movements to which they are inserted and affected by the consequences of all qualities. This way, the process of reading and scientific analysis of the sources becomes ingenious by the opposing of discourses sometimes full of ideologies proper to the movements. The research focused on understanding the topic from a bibliographical survey on the issue, analysis of the documents prepared by Paraná?s administration and field research carried out at the peasant liberation school and at State Country School Izaias Rafael da Silva, located in the settlement liberation Peasant, municipality of Ortigueira, in the region of the general countries of Paraná. To support our work, we use the concepts and categories of analysis, such as struggle, culture and resistance, based on the conceptions of the new history, on the studies of Gramsci, Thompson and Marx, as well as on the understanding of the articulated movements in network based on Castells? believes. Thus, in the light of this theoretical framework, the documents researched and the interviews carried out, it was possible to envisage social experiences and to experience, as well as to understand the fundamental role of social movements administrated in the creation and maintenance of public educational policies